Processed Transcript Insertion as a Novel Germline Mutational Mechanism in BRCA1 -Associated Hereditary Breast Cancer. - Bozsik, Anikó; Butz, Henriett; Grolmusz, Vince Kornél; Nagy, Petra; Pócza, Tímea; Tóth, Erika; Csernák, Erzsébet; Patócs, Attila; Papp, János (Cancers, 2025)
Simple Summary: Structural variations in cancer predisposition genes significantly contribute to the pool of pathogenic variants underlying heritable cancer susceptibility. In this report, we describe and functionally characterize a novel transposon-mediated germline pathogenic insertion identified within the coding region of the BRCA1 gene. The inserted sequence comprises the entire processed transcript of RPL18A, a ribosomal protein-coding gene, and may have been generated through a target-primed reverse transcription event. Robust molecular testing confirmed the heritability of the variant and provided evidence of its correlation with the observed phenotype. This is the first documented case of a germline cancer susceptibility variant arising through this unique mechanism. Background/Objectives: Germline BRCA1 mutations account for ~15–20% of hereditary breast and ovarian cancer (HBOC) cases. While most are small sequence variants, structural rearrangements also contribute significantly to the pathogenic landscape. Conventional diagnostic workflows often miss such events, underscoring the need for comprehensive approaches. Here, we report a previously undescribed pathogenic mechanism—a transposon-mediated processed transcript insertion—expanding the mutational spectrum underlying hereditary breast cancer susceptibility. Methods: The studied case was discovered during our germline genotyping routine: next-generation sequencing followed by library preparation with a custom hereditary cancer panel. The identified variant was validated by orthogonal sequencing and multiplex ligation-dependent probe amplification (MLPA). RNA-level functional assays, including nonsense-mediated decay inhibition, were conducted to assess transcript stability. Constitutional origin was confirmed by analysis of multiple normal tissues, and tumor material was evaluated for loss of heterozygosity (LOH). Results: NGS detected a 700 bp insertion in exon 16 of BRCA1, corresponding to a complete processed transcript of RPL18A. The insertion caused a frameshift and premature stop codon, triggering degradation of the aberrant transcript. The variant was present in multiple somatic tissues, and its heritable nature was further confirmed by genotyping a first-degree relative, who was also found to carry the insertion. Tumor DNA analysis revealed strong LOH with retention of the variant allele. Conclusions: This study identifies, for the first time, a heritable processed transcript insertion as a pathogenic event in BRCA1. Such variants are undetectable by conventional diagnostic workflows lacking structural variant analysis, highlighting the importance of comprehensive approaches for accurate diagnosis and genetic counselling in hereditary cancer syndromes.